2011
DOI: 10.1186/1744-8069-7-90
|View full text |Cite
|
Sign up to set email alerts
|

Hyperalgesic Activity of Kisspeptin in Mice

Abstract: BackgroundKisspeptin is a neuropeptide known for its role in the hypothalamic regulation of the reproductive axis. Following the recent description of kisspeptin and its 7-TM receptor, GPR54, in the dorsal root ganglia and dorsal horns of the spinal cord, we examined the role of kisspeptin in the regulation of pain sensitivity in mice.ResultsImmunofluorescent staining in the mouse skin showed the presence of GPR54 receptors in PGP9.5-positive sensory fibers. Intraplantar injection of kisspeptin (1 or 3 nmol/5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 57 publications
2
15
0
Order By: Relevance
“…This is in accordance with previous findings in hot plate and formalin tests conducted by Spampinato et al [206] and recent results that of Elhabazi et al [50]. In our experiments no linear dose-response curve, but rather an inverted bell-shaped response was observed, which is well known in the literature, and has already been described in case of endomorphins [22] and other neuropeptides [146].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This is in accordance with previous findings in hot plate and formalin tests conducted by Spampinato et al [206] and recent results that of Elhabazi et al [50]. In our experiments no linear dose-response curve, but rather an inverted bell-shaped response was observed, which is well known in the literature, and has already been described in case of endomorphins [22] and other neuropeptides [146].…”
Section: Discussionsupporting
confidence: 82%
“…Second, in chronic inflammatory pain model kisspeptin and KISS1R up-regulation was detected at the level of the dorsal root ganglia and dorsal horn neurones [140]. Third, Spampinato et al reported that the KISS1R antagonist, kisspeptin-234 exhibits a clearly analgesic effect in formalin test [206]. Fourth, the NPFFR agonist, NPFF in numerous studies caused analgesia when the route of administration was intrathecal instead of icv.…”
Section: Discussionmentioning
confidence: 99%
“…A few data indicate that KP has other actions besides that on reproduction. The hyperalgesic action of KP has been reported in mice [26]. KP directly regulates neuropeptide Y synthesis in hypothalamic neurons [27].…”
Section: Discussionmentioning
confidence: 99%
“…The capsaicin TRPV1 receptor is a non-selective ligand-gated cation channel that formed by six membrane-spanning domains assembled as homo or hetero-tetramers activated by heat, low pH, and endogenous lipids [2][3][4]. TRPV1 receptors are widely expressed in areas that are involved in pain transmission, both in the central and peripheral nervous system [5,6]. In the brain, TRPV1 receptors are also involved in the modulation of synaptic plasticity as well as in epilepsy and cognition [7].…”
Section: Introductionmentioning
confidence: 99%